1987
DOI: 10.3109/17453678709146338
|View full text |Cite
|
Sign up to set email alerts
|

Bone cement improved by vacuum mixing and chilling

Abstract: Two mixing methods, hand and vacuum mixing, were compared using high viscosity, high molecular, antibiotic containing polymethylmethacrylate kept at two different temperatures, 4 degrees C and 21 degrees C, prior to mixing. The mechanical properties, i.e., fracture strength, maximum deflection, modulus of elasticity and hardness, were improved by vacuum mixing when compared with hand mixing at both temperatures. The fatigue life was 10 times longer after vacuum mixing. Chilling prior to mixing made the mixing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
4

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(42 citation statements)
references
References 11 publications
2
35
1
4
Order By: Relevance
“…Vacuum mixing of bone cement is considered to be beneficial, as reduced porosity and improved physical properties of acrylic bone cements are achieved (Alkire et al 1987, Lidgren et al 1987, Schreurs et al 1988. Also, vacuum mixing devices are expected to reduce exposure to MMA vapours, as the mixing process is performed under vacuum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vacuum mixing of bone cement is considered to be beneficial, as reduced porosity and improved physical properties of acrylic bone cements are achieved (Alkire et al 1987, Lidgren et al 1987, Schreurs et al 1988. Also, vacuum mixing devices are expected to reduce exposure to MMA vapours, as the mixing process is performed under vacuum.…”
Section: Discussionmentioning
confidence: 99%
“…Vacuum mixing of polymethylmethacrylate (PMMA) bone cement is advocated to reduce voids and porosity within the cement mantle, which are suspected to contribute to crack development and prosthesis failure or loosening (Lidgren et al 1987, Wixson et al 1987, Geiger et al 2001. The vacuum mixing devices are connected to specific suction units and are thus also expected to minimise exposure to methylmethacrylate (MMA) monomer fumes evaporating during the mixing procedure (Darre et al 1988, Bettencourt et al 2001.…”
mentioning
confidence: 99%
“…For Palacos R, Lidgren et 25 2586 al. 101 and Hansen and Jensen 102 found that vacuum mixing 25 1872 slightly lowers and increases t s , respectively. Second, the 20 8377 effect of prechilling of the liquid monomer on the proper- 20 15 331 ties of bone cement remains controversial.…”
Section: Research Directionsmentioning
confidence: 99%
“…The influence of the temperature at which the either the package containing all cement constituents or only the ampoule containing the liquid-monomer constituents is stored prior to the mixing (T s ) on a cement's fatigue performance has been the subject of three systematic studies 18,30,31,60 ( Table III). Lidgren, Bodelind, and Moller 18 and Lewis 60 found that the fatigue lives for Palacos R with T s of 4 and 21°C were about the same.…”
Section: Effect Of Extrinsic Factors Storage Temperature Of Constituentsmentioning
confidence: 99%